2021
DOI: 10.1007/s00405-021-07120-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and survival of tracheostomised patients during the COVID-19 pandemic in a third level hospital

Abstract: Purpose Analyse the evolution and outcomes of COVID-19 tracheostomised patients. Clarify if this cohort presents an increased risk of haemorrhagic complications and verify the correlation between some risk factors with increased mortality. Methods A retrospective single-centre observational study of a prospective cohort of all COVID-19 patients admitted to our centre between March and April 2020. A control group was obtained from a historical cohort of patients who requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…16 The second of these studies found a significantly increased risk of bleeding in Covid-19 patients (20.3 per cent vs 5.97 per cent), but with no difference in length of hospital stay. 17 The final of these studies reported an increased time from intubation to tracheostomy in Covid-19 patients (25.4 days vs 22.9 days). 7…”
Section: Resultsmentioning
confidence: 98%
“…16 The second of these studies found a significantly increased risk of bleeding in Covid-19 patients (20.3 per cent vs 5.97 per cent), but with no difference in length of hospital stay. 17 The final of these studies reported an increased time from intubation to tracheostomy in Covid-19 patients (25.4 days vs 22.9 days). 7…”
Section: Resultsmentioning
confidence: 98%
“…In the present study, bleeding complications were observed in 7.5% of patients. In a previous retrospective single‐center observational study of a prospective cohort of patients with COVID‐19 in Spain, bleeding complications occurred in 20.31% of 64 patients with tracheostomized COVID‐19 13 . In a retrospective study of 161 COVID‐19 non‐survivors in Turkey, 39% had major bleeding complications.…”
Section: Discussionmentioning
confidence: 97%
“…1 A recent study of 1371 patients with COVID-19 found that 64 out of 330 (19.4%) patients admitted to the intensive care unit (ICU) eventually underwent tracheotomy. 2 Though tracheotomy is generally associated with an increase in survival, the high mortality rate of intubated patients with COVID-19 makes predicting which patients will survive beyond the immediate postoperative period challenging. 3,4 Previous studies have explored predictive factors for mortality in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%